Odpowiedzi

2009-11-12T20:32:59+01:00
2x³-6x²+x-3=0
2x²(x-3) +1(x-3)=0
(2x²+1)(x-3)=0
2x²+1 = 0 v x-3 =0
x²= -0,5 sprzeczność(kazda liczba podniesiona do ² jest dodatnia) v x=3

x=3

2009-11-12T20:46:08+01:00
A)2x³-6x²+x-3=0
2x²(x-3)+(x-3)=0
(x-3)*(2x²+1)=0
x-3=0 ∨ 2x²+1=0
x=3∨x∈Ф
b)3xdo4potęgi+6x²-8x²+2x-3=0
p:±1,±3
q:±1,±3
p/q:±1,±3±1/3
W(1)=3*1+6
*1-8*1+2*1-3=0
3xdo4potegi+6x³-8x²+2x-3÷(x-1)=3x³+9x²+x+3
-3xdo4potegi+3x³
_______________
= 9x³-8x²
-9x³+9x²
____________________
= x²+2x
-x²+x
____________________
= 3x-3
-3x+3
_________________________
= =
3x³+9x²+x+3=0
3x²(x+3)+x+3=0
(x+3)*(3x²+1)=0
x=-3∨x∈Ф

czyli x=1∨x=-3